1997
DOI: 10.1007/bf03012771
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous fentanyl PCA during labour

Abstract: To evaluate the usefulness of intravenous patient-controlled analgesia (PCA) fentanyl for labour analgesia, its effectiveness for maternal pain and safety for the fetus and newbom.Methods: Twenty primigravidas were randomised to receive intravenous PCA fentanyl or epidural analgesia for labour pain. Maternal pain, heart rate and arterial oxyhaemoglobin saturation (Sp02) were monitored. Fetal and neonatal monitoring induded cardiotocogram (CTG), APG/~ neurological scoring and static-charge-sensitive bed (SCSB) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 34 publications
2
45
0
1
Order By: Relevance
“…Sharma et al (1997) reported median (25 th -75 th percentiles) sedation scores of 0 (0-0) and 1 (0-2) in EDA and pethidine IVPCA groups in a large study including 715 parturients on a categorical observer scale (0 = awake and alert, 1 = awake but drowsy, 2 = asleep but arousable, 3 = asleep but difficult to arouse, 4 = unresponsive) (p < 0.001). This finding was consistent with other studies comparing EDA with long-acting systemic opioids (Sharma et al 1997, Nikkola et al 1997, Jain et al 2003, Halpern et al 2004.…”
Section: Sedationsupporting
confidence: 93%
See 1 more Smart Citation
“…Sharma et al (1997) reported median (25 th -75 th percentiles) sedation scores of 0 (0-0) and 1 (0-2) in EDA and pethidine IVPCA groups in a large study including 715 parturients on a categorical observer scale (0 = awake and alert, 1 = awake but drowsy, 2 = asleep but arousable, 3 = asleep but difficult to arouse, 4 = unresponsive) (p < 0.001). This finding was consistent with other studies comparing EDA with long-acting systemic opioids (Sharma et al 1997, Nikkola et al 1997, Jain et al 2003, Halpern et al 2004.…”
Section: Sedationsupporting
confidence: 93%
“…Surprisingly, only three RCTs comparing EDA with systemic opioid analgesia (table 2) have employed the measurement of SaO 2 or other ways to show an effect on respiration, probably reflecting the fact that the obstetric outcome was the primary end point in most of the studies. Nikkola et al (1997) noted a SaO 2 > 95% in all parturients receiving either EDA with 0.5% bupivacaine or IVPCA fentanyl. Jain et al (2003) did not report any parturient with a respiratory rate < 8 when EDA was compared with intramuscularly administered opioids.…”
Section: Respiratory Effectsmentioning
confidence: 90%
“…Similar degrees of analgesia have been shown in other studies; however, most of these studies evaluated analgesic efficacy only for the first two to three hours after initiation of PCA. [10][11][12][13][14]25 One possible explanation for an increase in pain scores towards the end of labour in our study was the practice of continuing PCA into the second stage of labour when the intensity and frequency of pain are likely to be greater. Douma et al 10 observed superior analgesia with remifentanil compared with fentanyl in labouring patients; however, the difference was evident only during the first hour of treatment, and pain scores returned to baseline values in both groups within three hours of initiation of PCA.…”
Section: Discussionmentioning
confidence: 78%
“…34 Despite the lack of visible neonatal depression at birth, during a 12-hr monitoring period after birth, Nikkola et al observed numerous events of desaturation (SpO 2 B 90%) in neonates of mothers who received fentanyl PCA. 25 This indicates the potential for fentanyl-due to its long half-life-to cause delayed respiratory depression in neonates after PCA use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation